2017
DOI: 10.1111/jse.12230
|View full text |Cite
|
Sign up to set email alerts
|

Increased novel single nucleotide polymorphisms in weedy rice populations associated with the change of farming styles: Implications in adaptive mutation and evolution

Abstract: Substantial genetic variation is found in weedy rice (Oryza sativa f. spontanea Roshev.) populations from different rice‐planting regions with the change of farming styles. To determine the association of such genetic variation with rice farming changes is critical for understanding the adaptive evolution of weedy rice. We studied weedy‐rice specific novel single nucleotide polymorphisms (SNPs) by genome‐wide comparison between DNA sequences of weedy and cultivated rice, in addition to polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…In addition, the close genetic relationship between SL WR and cultivated rice is probably due to the relatively few rice varieties with a similar genetic background to WR in this country (Xu et al, ). This is different from rice farming in China, where changes of rice varieties, even from indica to japonica varieties, are frequently taking place in many rice‐planting regions, particularly in JS province (Nai et al, ; Song et al, ). We therefore conclude that both geographical distribution and cultivar types have significantly influenced genetic differentiation of WR populations across the rice‐planting regions included in this study.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In addition, the close genetic relationship between SL WR and cultivated rice is probably due to the relatively few rice varieties with a similar genetic background to WR in this country (Xu et al, ). This is different from rice farming in China, where changes of rice varieties, even from indica to japonica varieties, are frequently taking place in many rice‐planting regions, particularly in JS province (Nai et al, ; Song et al, ). We therefore conclude that both geographical distribution and cultivar types have significantly influenced genetic differentiation of WR populations across the rice‐planting regions included in this study.…”
Section: Discussionmentioning
confidence: 98%
“…This result supports the multiple origins of the WR populations in JS province, most likely through introgression from cultivated rice (Xia et al, ; Sun et al, ), as well as dedomestication as suggested by Li et al () and Qiu et al (). The gradual transition from the traditional way of growing indica types of rice cultivars to the current cultivation of japonica types of cultivars over the past several decades (Nai et al, ; Song et al, ) might have promoted the change in the genetic diversity and structural patterns of WR in the JS region. Previous studies also documented such a change from the indica to japonica type of WR plants (Song et al, ), and increased single nucleotide polymorphisms in WR populations in JS province (Song et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a few seasons later, a large occurrence of escapees was observed again, which may be associated with the ALS alleles Ala122Thr and Ser653Asn carried by current CL rice cultivars. These results are related to the introgression among cultivated and red (Song et al, 2017) and wild rice , which is a challenge for the sustainability of technologies for herbicide-tolerance in rice crop.…”
Section: Resultsmentioning
confidence: 99%